Assessing female call responses to syllable level details in song - Prior, Nora H.; Fishbein, Adam R.; Garcia, Esther Martinez; Clough, Savannah; Elson, Mary R.; Ball, Gregory F.; Dooling, Robert J. (Frontiers in Psychology, 2025)
Mate choice is a critical decision-making process, having lasting impacts on an individual’s time, energy, and reproductive success. Across songbirds, females are generally assumed to prefer higher song rates, greater complexity, and higher quality performances; however, there is growing evidence implicating syllable level details in songbird communication. Here, we build on our previous psychoacoustic results to ask whether female zebra finches use the kinds of syllable level details that they are capable of hearing. Female zebra finches produce calls during male songs as a component of courtship. These calls can be leveraged to explore how females assess and interact with male songs. To test whether syllable level details are behaviorally relevant in a courtship context, we quantified female call responses to manipulated songs in four experiments. First, we validated that our playback procedure elicited robust calling responses from females (Exp 1). Next, we found that females decreased calling to songs where syllables were spectro-temporally reversed (REVERSAL), but did not respond differently if the syllable order was manipulated (SHUFFLED). Females also modulated their calling when experimental songs were composed of natural rendition-to-rendition variation in song syllables (RENDITION) relative to songs consisting of a single repeated rendition (FIXED) (Exp 2). Furthermore, we found that females decreased calling responses even when only a portion of syllables were spectro-temporally reversed (Exp 4). Across these experiments, we also report the striking extent to which females habituated to a male’s song (Exps 3 and 4). To maximize female responses, we tried adjusting the paradigm in Exps 3 and 4 to increase female calling. However, our adjustments had minimal effects, consistent with the notion that females rapidly decreased calling in response to a given males’ stimuli. Altogether, our results contribute to growing evidence that syllable level details in birdsong are behaviorally relevant, and, perhaps more importantly, demonstrate that birds’ enhanced ability to discriminate acoustic fine structure as shown in psychophysical tests plays a role in communication.